Photoactive dye‐enhanced tissue ablation for endoscopic laser prostatectomy. Issue 9 (28th August 2014) - Ahn, Minwoo; Hau, Nguyen Trung; Van Phuc, Nguyen; Oh, Junghwan; Kang, Hyun Wook
<x xml:space="preserve">Abstract</x> Background and Objective Laser light has been widely used as a surgical tool to treat benign prostate hyperplasia (BPH) over 20 years. Recently, application of high laser power up to 200 W was often reported to swiftly remove a large amount of prostatic tissue. The purpose of this study was to validate the feasibility of photoactive dye injection to enhance light absorption and eventually to facilitate tissue vaporization with low laser power. Materials and Methods Chicken breast tissue was selected as a target tissue due to minimal optical absorption at the visible wavelength. Four biocompatible photoactive dyes, including amaranth (AR), black dye (BD), hemoglobin powder (HP), and endoscopic marker (EM), were selected and tested in vitro with a customized 532 nm laser system with radiant exposure ranging from 0.9 to 3.9 J/cm2. Light absorbance and ablation threshold were measured with UV–Vis spectrometer and Probit analysis, respectively, and compared to feature the function of the injected dyes. Ablation performance with dye‐injection was evaluated in light of radiant exposure, dye concentration, and number of injection. Results Higher light absorption by injected dyes led to lower ablation threshold as well as more efficient tissue removal in the order of AR, BD, HP, and EM. Regardless of the injected dyes, ablation efficiency principally increased with radiant exposure, dye concentration, and number of injection. Among the dyes, AR created the highest ablation rate of 44.2 ± 0.2 µm/pulse due to higher absorbance and lower ablation threshold. High aspect ratios up to 7.1 ± 0.4 entailed saturation behavior in the tissue ablation injected with AR and BD, possibly resulting from plume shielding and increased scattering due to coagulation. Preliminary tests on canine prostate with a hydraulic injection system demonstrated that 80 W with dye injection yielded comparable ablation efficiency to 120 W with no injection, indicating 33% reduced laser power with almost equivalent performance. Conclusion Due to efficient coupling of optical energy, pre‐injection of photoactive dyes promoted the degree of tissue removal during laser irradiation. Further studies will investigate spatial distribution of dyes and optimal injecting pressure to govern the extent of dye‐assisted ablation in a predictable manner. In‐depth comprehension on photoactive dye‐enhanced tissue ablation can help accomplish efficient and safe laser vaporization for BPH with low power application. Lasers Surg. Med. 46:703–711, 2014. © 2014 Wiley Periodicals, Inc.